Characterization of Multiple Grain Rice (Oryza sativa L.) Biramsundari from Bangladesh (Plant Tissue Culture and Biotechnology, 2022)
Biramsundari is a rice germplasm from Bangladesh showing one to four grain in a single seed. Comparative study of morphological traits revealed that BS is a taller rice variety compared to modern rice varieties with longer and wider flag leaves, longer panicle length and higher thousand seed weight (TSW) than transplanted aman rice variety BRRI dhan 49. Flower morphological analysis unveil that multiple grains of Biramsundari are originating from multiple number of carpels in each floret. About 40.1% flower contains three carpels. Fluorescent microscopic study also confirms the zygotic origin of multiple grain formation in Biramsundari. Molecular characterisation of Biramsundari was performed by using TeaCpSSR27 and TeaCpSSR28 chloroplast microsatellite markers. The results of this investigation reveal that atpF and rsp14-psaB intergenic spacer regions of Biramsundari have variation compared to sequences of with O. sativa ssp. indica, O. sativa ssp. japonica and O. rufipogon.Plant Tissue Cult. & Biotech. 31(2): 115-122, 2021 (December)